2015
DOI: 10.32607/20758251-2015-7-1-102-108
|View full text |Cite
|
Sign up to set email alerts
|

Selective Protective Potency of Yersinia pestis ΔnlpD Mutants

Abstract: It has recently been shown that the NlpD lipoprotein is essential to Yersinia pestis virulence and that subcutaneous administration of the nlpD mutant could protect mice against bubonic and pneumonic plague better than the EV vaccine strain [PLoS One 2009. V. 4. № 9. e7023]. In this study, similar ΔnlpD mutants were generated on the basis of other Y. pestis parent strains, including strains from the subspecies microtus, which is avirulent to guinea pigs and humans. Comparative testing confirmed that immunizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Lipoprotein NlpD of Y. pestis is an essential virulence factor for the development of bubonic and pneumonic plague. 53,54 Subcutaneous administration of the Δ nlpD Y. pestis Kimberley53 mutant conferred protection to mice against bubonic and pneumonic plague better than the EV76 vaccine strain. 53 Dentovskaya et al generated a variety of Δ nlpD mutant strains based on three Yersinia parental strains (i.e., subsp.…”
Section: Attenuated Yersinia Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…Lipoprotein NlpD of Y. pestis is an essential virulence factor for the development of bubonic and pneumonic plague. 53,54 Subcutaneous administration of the Δ nlpD Y. pestis Kimberley53 mutant conferred protection to mice against bubonic and pneumonic plague better than the EV76 vaccine strain. 53 Dentovskaya et al generated a variety of Δ nlpD mutant strains based on three Yersinia parental strains (i.e., subsp.…”
Section: Attenuated Yersinia Vaccinementioning
confidence: 99%
“…In comparison to the reference vaccine strain EV NIIEG, immunization with the Δ nlpD mutant strains provided potent protective immunity against plague in BALB/c mice challenged with 200 LD 100 of virulent Y. pestis 231 strain, but failed to do so in the guinea pig model. 54 The intrinsic reasons are not clear yet, but the inconsistent protection observed in different animal models diminishes the possibility of Δ nlpD Y. pestis mutant as one of the live plague vaccine candidates.…”
Section: Attenuated Yersinia Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a Y. pestis ΔyopH mutant is attenuated and provides a high level of protection against bubonic and pneumonic plague in mice [133]. Studies showed that Δpcm and ΔnlpD mutants were attenuated and elicited protective immunity in mice [134, 135], but the immunization with ΔnlpD mutants failed to protect guinea pigs [136]. …”
Section: Live Attenuated Yersinia Vaccinesmentioning
confidence: 99%
“…At the same time, Y. pestis has been recognized as a Tier 1 select biological agent due to its potential use as a bioweapon (Inglesby et al, 2000 ). The severity of the disease in combination with concerns regarding the existence of antibiotic-resistant Y. pestis strains has prompted efforts to develop safe live vaccines (Titball and Williamson, 2004 ; Feodorova et al, 2007 ; Tidhar et al, 2009 ; Feodorova and Motin, 2012 ; Dentovskaya et al, 2015 ; Derbise et al, 2015 ; Tiner et al, 2016 ; Verma and Tuteja, 2016 ).…”
Section: Introductionmentioning
confidence: 99%